Flight safety risks normalization on civil aviation aerodromes - Дев’яткіна, С.С. (Proceedings of National Aviation University (archive), 2010)
Main problems of flight safety risks normalization on civil aviation aerodromes are considered. Their urgency is proved and ways of solving are suggested.